ANALISIS LEVEL KEMAMPUAN COMPLEX PROBLEM SOLVING MAHASISWA CALON GURU MATEMATIKA - Megita Dwi Pamungkas; Fadhilah Rahmawati; Irka Lestari; Kristina Warniasih (Universitas Muhammadiyah Semarang, 2023)
Complex problem solving is a cognitive skill to obtain information about obscure problem situations and use knowledge to achieve self-formulated goals in solving problems. The purpose of this study is to describe the level of complex problem-solving ability of students who are prospective mathematics teachers. This research uses descriptive qualitative methods. The subjects of this study were 3 prospective mathematics teacher students in semester VII of the Mathematics Education Study Program at Tidar University. The main instrument is the researcher himself, supported by complex problem-solving tests and interview guidelines. The data studied are answer sheets for complex problem solving tests which are then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the level of complex problem-solving ability is divided into 3, namely novice, medium, and proficient.